Assessment of a diabetes education program on knowledge of diabetes among diabetics attending a government hospital in Turkey - Soylar, Pınar; Özer, Ali (SEAMEO TROPMED Network, 2019)
It is important for diabetics to understand their disease and how to prevent its complications. The aim of this study was to assess the efficacy of a diabetes education program on knowledge of diabetes among diabetic patients attending a government hospital in Turkey in order to inform program organizers about deficiencies and strengths of the program and how to improve it. A multidisci-plinary team at a government hospital developed a diabetes educational program for diabetic patients following the 5 modules of the Turkey Diabetes Program (2015-2020). The study subjects consisted of patients with diabetes mellitus type 2 (T2DM) attending the diabetes outpatient clinic, Malatya State Hospital and were willing to participate in the all sessions of the education program and willing to complete the pre-and post-program questionnaire. All the eligible subjects were invited to participate (n=276) whom 185 completed the program and filled out the questionnaire. The mean [± standard deviation (SD)] age of study subjects was 56.3 (±9.9) years; 54.6% males. The mean questionnaire score prior the program was 6.3 points and after the program was 11.7 points; this difference was significant (p<0.001). The mean questionnaire score in males prior to the program (6.6 points) was significantly higher (p=0.020) than the female subjects (6.0 points) but after the program the mean questionnaire score among males (11.8 points) was not significantly higher than the female subjects (11.5 points) (p=0.334). The mean questionnaire score prior to program among subjects with a higher education level (7.2 points) was significantly higher (p=0.002) than among subjects with a lower education level (5.9 points) but the questionnaire score after the program among subjects with a higher education level (11.9 points) was not significantly different (p=0.323) from those with a lower education level (11.6 points). We conclude the diabetes education program was effective in improving knowledge about T2DM and it corrected disparities in knowledge level by gender and education level. Further studies are needed to determine if this improved in knowledge level is retained over time and if it results in a measurable effect on the level of diabetes control and the prevelance of complications. © 2019, SEAMEO TROPMED Network. All rights reserved.
Keywords: Diabetes education; Diabetes mellitus; Educational status